A new genus and new species of Potamidea (Crustacea: Decapoda: Brachyura: Potamoidae), the first stygomorphic cave crab known from China and East Asia - Huang, Chao; Shih, Hsi-Te; Ng, Peter K. L. (Zootaxa, 2017)
A new genus and species of freshwater crab, Diyutamon cereum n. gen., n. sp., is described from a cave in Guizhou, China. This is the first record of a true stygomorphic crab from China and East Asia, possessing pale body coloration, strongly reduced eyes, and long ambulatory legs. While superficially similar to Chinapotamon Dai & Naiyanetr, 1994, and Tiwaripotamon Bott, 1970, the new genus possesses a diagnostic combination of carapace, ambulatory leg, thoracic sternal, and male abdominal characters that easily distinguishes it from other genera. Molecular data derived from the mitochondrial 16S rDNA supports the establishment of the new genus.